Effectiveness of acupuncture for vascular cognitive impairment no dementia: a randomized controlled trial. (April 2019) - Yang, Jing-Wen; Shi, Guang-Xia; Zhang, Shuai; Tu, Jian-Feng; Wang, Li-Qiong; Yan, Chao-Qun; Lin, Lu-Lu; Liu, Bao-Zhen; Wang, Jun; Sun, San-Feng; Yang, Bo-Feng; Wu, Li-Yu; et al.
Objective: To evaluate the effectiveness of acupuncture in patients with vascular cognitive impairment no dementia (VCIND) in comparison with citicoline, an agent for cognitive disturbances associated with chronic cerebral disorders. Design: A randomized controlled multicenter trial. Setting: In three hospitals in Beijing, China. Subjects: A total of 216 patients with VCIND were recruited. Interventions: Patients with VCIND (mean age of 65.4 years) were randomized to receive acupuncture (two sessions per week) or oral citicoline (100 mg three times daily) over three months. Main measures: The primary outcome was the change from baseline to three months in cognitive symptom, measured by Alzheimer's disease Assessment Scale, cognitive subscale (ADAS-cog). Secondary outcomes included changes from baseline to six months in ADAS-cog, executive function measured by the Clock Drawing Test (CDT), and functional disability measured by the Ability of Daily Living (ADL) scale at three and six months. Results: At three months, the acupuncture group had a greater decrease in mean ADAS-cog score (−2.33 ± 0.31) than the citicoline group (−1.38 ± 0.34) with a mean difference of −0.95 (95% CI, −1.84 to −0.07, P  = 0.035). The mean change from baseline to six months in ADAS-cog also significantly favored acupuncture treatments (acupuncture change −2.61 vs citicoline −1.25, difference: −1.36 points; 95% CI, −2.20 to −0.51; P  = 0.002). There was no difference between the two groups on CDT and ADL scores at either time point. Conclusion: Compared with citicoline, acupuncture has comparable and even superior efficacy with improved cognitive and daily living performance as a complementary and alternative medicine treatment for VCIND.